FORMULATION OF DRAWINGS (DRYMOGLOSSUM PILOSELLOIDES L. PRESL) ETHANOL EXTRACT OF ACNE GEL ON THE GROWTH OF THE BACTERIA PROPIONIBACTERIUM ACNES - Harnis, Zola Efa; Nina Irmayanti Harahap; Rika Puspita Sari; Sarviana Lubis (Sean Institute, 2022)
Dragon scales (Drymoglossum piloselloides L. Presl) is a plant that has antibacterial activity against the bacteria Propionibacterium acnes and Staphylococus aureus, Bacillus subtilis, Escherichia coli, and Streptococcus pneumonia. The content of compounds that act as antibacterial are saponins, polyphenols, essential oils, sterols / triterpenes, phenols, flavanoids, sugars and tannins. This study aims to make a formula of dragon scales ethanol extract gel against the growth of propionibacterium acnes bacteria. The method used in this study was experimental laboratory. The formulation of dragon scales ethanol extract gel is made with a concentration variation of 5%, 10%, 15%. Antibacterial activity test is carried out with diffusion agar.